V.I. Lenin, guest of A.M. Gorki, playing chess with A.A. Bogdanov in Capri, Italy . From left to right sitting: I.P. Ladyžnikov, V.I. Lenin, A.A. Bogdanov; standing: V.A. Bazarov ('Rudnev'), A.M. Gor'kij, Z.M. Peškov, N.B. Bogdanova. Compare: 69/39 A, page 33 - Željabužskij, Ju.A.,
V.I. Lenin, guest of A.M. Gorki, playing chess with A.A. Bogdanov in Capri, Italy . From left to right sitting: I.P. Ladyžnikov, V.I. Lenin, A.A. Bogdanov; standing: V.A. Bazarov ('Rudnev'), A.M. Gor'kij, Z.M. Peškov, N.B. Bogdanova. Compare: 69/39 A, page 33.